Biodeterioração de tintas látex com e sem biocida, expostas ao meio ambiente externo e experimento acelerado - Silva, Flayane Hoehr (2009)
The aim of this work is the fungal contamination assessment on mortar painted with waterborne paint with and without biocide, this material is widely used in building. The identification of the commonest fungal species in this region and during one year and the biofilm gradual development was analysed and environment temperature, superficial temperature and humidity were also evaluated. Beyond the environment experiment, paper painted with 7 waterbonr paint were setting in controlled environment. The results showed that the main contaminants were Cladosporium sp. e Penicillium sp., that were settled on paint during all seasons. The others contaminants were: Alternaria sp., Aspergillus nigrum e A. aureum, Curvularia sp., Phoma sp. e Epicoccum nigrum and two fungal mycelia. In the environmental experiment, the best performance was paint 7, halb-brightness paint, commercially called first line. The controlled experiment showed that it needs a better development for its application, because it had a diverse results in relation to the field assay.